Expressed Emotion as Moderator Between Openness to Experience and Help-Seeking Attitude Towards Telepsychology of Filipino Generation Zoomers - Barcelon, Erice Sampaga; Abril, Princess Kayla Escalante; Alcaraz, Ma. Patricia Romero; Tripoli, Maryrose Elaine Mendoza; Autriz, Arianne Espiritu (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
This study aimed to explore whether expressed emotion moderates Generation Z's openness to experience and help-seeking attitude toward telepsychology and the extent to which the expressed emotion modifies that relationship. A total of 395 people belonging to the said generation participated in an online survey accomplished through Google Forms. The study used a correlational research method that focused on moderation to examine the relationship between Generation Z's openness to experience and their attitude toward telepsychology. Hence, this study sought to increase Generation Z's knowledge of mental health, including Philippine mental health conditions, as they develop a sense of responsibility, reduce ambiguity through telepsychology platforms, and improve their communication skills, which are crucial for ideal emotional socialization. Results have shown that expressed emotion does not seem to have a noticeable effect on Generation Z's attitudes toward seeking help through telepsychology. Nevertheless, there was a favorable correlation between being open to new experiences and having a willingness to seek help through telepsychology. The study adds to the growing body of knowledge on the mental health dynamics of Filipino Generation Z, and it offers beneficial information for the generation, professionals in mental healthcare, educators, and policymakers looking for enhanced support systems and interventions that meet the specific psychological needs of Filipino Generation Zoomers. Keywords: expressed emotion; generation z; help-seeking attitude; openness to experience; telepsychology